2019
DOI: 10.1038/s41598-019-39196-0
|View full text |Cite
|
Sign up to set email alerts
|

A complex interaction between pre-harvest and post-harvest factors determines fresh-cut melon quality and aroma

Abstract: Melons are prized for their characteristic aroma, however, pre-harvest growth, stage of ripening at harvest, post-harvest processing and storage conditions lead to quality changes in fresh-cut fruit. We considered changes in metabolites and gene expression over 14 days storage to assess underlying mechanisms and identify potential quality markers. Overall, 99 volatile organic compounds (VOCs) were detected and VOC profiles discriminated between two melon seasons, cut-size, storage temperatures and storage time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Moreover, SPME is based on an equilibrium process, making quantitative analyses of VOC profile changes more challenging, and can suffer from saturation. In our work on fruit aroma 47 we have favoured the use of thermal desorption tubes for capturing VOCs directly from whole or minimally processed samples, and in peach this has also proven to be feasible 48 revealing important changes in VOC composition through storage.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SPME is based on an equilibrium process, making quantitative analyses of VOC profile changes more challenging, and can suffer from saturation. In our work on fruit aroma 47 we have favoured the use of thermal desorption tubes for capturing VOCs directly from whole or minimally processed samples, and in peach this has also proven to be feasible 48 revealing important changes in VOC composition through storage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are two types of fruit ripening, climacteric and non-climacteric, which have distinct regulatory mechanisms in determining organoleptic properties (McMurchie et al 1972). Melon is an important species to study these differences because it presents both phenotypes, having climacteric cultivars that are generally more aromatic having esters as the most prominent volatiles, while the non- Spadafora et al 2019). However, this is the rst study that presents an integrative analysis of metabolomics and gene expression of biochemical pathways related to volatile compound synthesis of non-climacteric ('Yellow') and climacteric ('Gaúcho') melons.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway biosynthesis of volatile aromas begins from 5 DAA (Day After Anthezise) to 35 (DAA) and the Cm-AAT gene is expressed very strong at the end of fruit development (Guo et al 2017;Yano et al 2018). The expression of Cm-AAT1 and Cm-AAT2 genes was reported to decrease with storage time (Spadafora et al 2019) and this was observed in the 'Hikadi' CmAAT1 gene, while in 'Hikapel' the CmAAT1 gene expression is still increased until the 10th day during storage (Figure 3). This indicates a delay in the process of biosynthesis of ester compounds so that the aroma of the 'Hikadi' melon dominates qualitatively at the time of measurement.…”
Section: Analysis Of Cm-aat1 Gene Expression From Melon Cultivars 'Himentioning
confidence: 99%
“…The expression of the Cm-AAT1 gene in melons was higher than the three genes of its family (Cm-AAT2, Cm-AAT3, and Cm-AAT4) and it was also known that the expression of the Cm-AAT3 gene was much lower than the others (Sharkawy et al 2005). Spadafora et al (2019) have also used the qRT-PCR method to look at the expression of CmAAT1 and CmAAT2 genes in melons with several treatment interactions between pre-harvest and post-harvest.…”
Section: Introductionmentioning
confidence: 99%